Paraclinical Aspects in Systemic Sclerosis - Bobeica C; Niculet E; Musat CL; Craescu M; Stefanescu BI; Dinu C; Chiscop I; Chirobocea S; Nechita L; Iancu AV; Stefanescu V; Balan G; et al. (International Journal of General Medicine, 2022)
Carmen Bobeica,1,* Elena Niculet,1,2 Carmina Liana Musat,1 Mihaela Craescu,1,* Bogdan Ioan Stefanescu,3,* Ciprian Dinu,4,* Iulia Chiscop,3,* Silvia Chirobocea,5,* Luiza Nechita,6,* Alina Viorica Iancu,1,* Victorita Stefanescu,7,* Gabriela Balan,6,8,9,* Ioana Anca Stefanopol,1,10,* Ana Maria Pelin,11,* Alin Laurentiu Tatu2,6,12 1Department of Morphological and Functional Sciences, Faculty of Medicine and Pharmacy, “Dunărea de Jos” University of Galați, Galati, 800008, Romania; 2Multidisciplinary Integrated Center of Dermatological Interface Research MIC-DIR (Centrul Integrat Multidisciplinar de Cercetare de Interfata Dermatologica - CIM-CID), “Dunărea de Jos” University, Galați, 800008, Romania; 3Clinical Surgical Department, Faculty of Medicine and Pharmacy, “Dunărea de Jos” University, Galați, Romania; 4Dental Department, Faculty of Medicine and Pharmacy, Dunărea de Jos University, Galați, Romania; 5Department of Neurology, Municipal Emergency Hospital, Moinești, Romania; 6Clinical Medical Department, Faculty of Medicine and Pharmacy, Dunărea de Jos University, Galați, Romania; 7Medical Department, Faculty of Medicine and Pharmacy, Dunărea de Jos University, Galați, Romania; 8Department of Gastroenterology, “Sf. Apostol Andrei” County Emergency Clinical Hospital, Galați, Romania; 9Research Center in the Field of Medical and Pharmaceutical Sciences, “Dunărea de Jos” University, Galați, Romania; 10Department of Pediatrics, Clinical Emergency Hospital for Children “Sf. Ioan”, Galati, Romania; 11Department of Pharmaceutical Sciences, Faculty of Medicine and Pharmacy, “Dunărea de Jos” University, Galați, Romania; 12Dermatology Department, “Sf. Cuvioasa Parascheva” Clinical Hospital of Infectious Diseases, Galați, Romania*These authors contributed equally to this workCorrespondence: Elena Niculet; Carmina Liana Musat, Department of Morphological and Functional Sciences, Faculty of Medicine and Pharmacy, “Dunărea de Jos” University of Galați, 35 Alexandru Ioan Cuza Street, Galați, 800008, Romania, Tel +40741398895 ; +40723338438, Email helena_badiu@yahoo.com; carmina.musat@ugal.roAbstract: Systemic sclerosis (SSc) is a chronic inflammatory disease with an autoimmune substrate that affects the skin and a large number of internal organs. The chronic inflammatory process is sustained by a wide range of cytokines and chemokines, which are discharged by inflammatory cells, with fibrosis and nail bed vascular changes (disorganized vasculature architecture with microhemorrhages, megacapillaries and areas without capillaries). Confocal microscopy contributes to the understanding of the molecular mechanism involved in chronic inflammation and mainly targets the field of research. Coherent optical tomography, capillaroscopy, and skin biopsy are useful for the differential diagnosis of SSc with other sclerodermoid syndromes. The immunological profile is a classification criterion for SSc and directs the diagnosis to the two subsets of the disease. Multisystemic damage requires evaluation with the help of a set of investigations specific to each affected organ, such as: diffusing capacity for carbon monoxide, forced vital capacity, 6-minute walk test, high-resolution computed tomography standard and reduced sequential, cardiac ultrasound and right cardiac catheterization. The current possibilities of diagnosis, treatment and monitoring are permanently adapting to new medical discoveries.Keywords: systemic sclerosis, antinuclear antibodies, capillaroscopy, confocal microscopy, coherent optical tomography